Appendix 4.13: Marcos Diary Entry, 19 December 1972 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
The eyes and ears of Marcos—at least in the judiciary and the military—are listed in this entry, dated nearly three months after he declared martial law. Again, in a caucus with “the original planners of martial law,” he dangles the possibility of establishing a revolutionary government if the Supreme Court proves to be troublesome. Marcos knew how to preach to the choir; it seems that in front of soldiers, he was the ruthless commander-in-chief, while before justices, he was, more often than not, the strict constitutionalist.